Changes in antibody titers and clinical course in myasthenia gravis retrospective study. Issue 1 (6th February 2022) - Berger, Benjamin; Schröter, Nils
Abstract : Myasthenia gravis (MG) is a rare, long‐term autoimmune disorder that causes muscle weakness; the condition typically has phases when it remits and phases when it relapses. Even though treatment response with regards to immunosuppressive therapies in MG patients is classically monitored by clinical scores, identification of a serological biomarker that monitors treatment response could be helpful. Here, the authors explore the correlation between acetylcholine receptor (AChR) antibody titers with changes in clinical severity in patients with MG and discuss the implications for clinical practice.